Generational differences and importance of workplace flexibility - Tshabalala, Tshidi (My University, 2023)
The aim of the study was to investigate generational differences and the importance of workplace flexibility, and the extent to which these differences vary across countries and cultures. The notion of generational differences in the workplace has emerged as an area of interest that has been widely studied by modern researchers, mainly because generational differences are thought to influence the behaviour and attitudes of employees in the workplace (Smola and Sutton, 2002). The largest diversity of generations is represented in today’s workplace than any other time in history (Glass, 2007). At present, four generations are working together in organisations across the world. These include Baby Boomers, Generation X, Generation Y and Traditionalist (Codrington and Grant-Marshall, 2006). These generations grew up in a different time period, as a result, may have different worldviews, and work expectations. I conducted a study using open access multinational data with a sample consisting of employees from 7 multinational companies across 11 different countries in Asia, Africa, South America, North and Europe. The final sample consisted of 11,298 respondents, ranging from 17 to 65 years of age and consisted of both full time and part time employees. The initial study administered and distributed a questionnaire to the participants to identify the demographic features of the study (See Appendix A) and the workplace A flexibility questionnaire was used to assess the flexibility perceptions of four generational cohorts (See Appendix B). Data was analysed by means of Kruskal-Wallis test to determine differences between the four generational cohorts. Spearman rankorder correlations were performed to determine the relationships between workplace flexibility, age and culture. The results of the current study revealed a non-significant relationship between workplace flexibility, age, culture and generations in a multinational sample. Overall, these results suggest that the importance of workplace flexibility may not significantly differ across the generational cohorts and across different country cultures. This may mean that people across different generational group and countries may have similar desires for flexible work practices, however age may make a small difference in this relationship which may indicate that as people get older, they may tend to prefer workplace flexibility for variety of reasons related to health and work-life balance.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Industrial/Organisational Psychology to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: Generational cohorts; Generation X; Generation Y